Answer:4x2−6x−4
Step-by-step explanation:
(4x+2)(x−2)
=(4x+2)(x+−2)
=(4x)(x)+(4x)(−2)+(2)(x)+(2)(−2)
=4x2−8x+2x−4
=4x2−6x−4
Our P = 100, r = .08, n = 1 (annually means once a year), and t = 15. Filling in accordingly, we have
![A(t)=100(1+ \frac{.08}{1})^{(1)(15)}](https://tex.z-dn.net/?f=A%28t%29%3D100%281%2B%20%5Cfrac%7B.08%7D%7B1%7D%29%5E%7B%281%29%2815%29%7D%20)
. Simplifying a bit gives us
![A(t)=100(1+.08)^{15}](https://tex.z-dn.net/?f=A%28t%29%3D100%281%2B.08%29%5E%7B15%7D)
and
![A(t)=100(1.08)^{15}](https://tex.z-dn.net/?f=A%28t%29%3D100%281.08%29%5E%7B15%7D)
. Raising that number inside the parenthesis to the 15th power gives us
![A(t)=100(3.172169114)](https://tex.z-dn.net/?f=A%28t%29%3D100%283.172169114%29)
. Multiplying to finish means that A(t) = $317.22
Y2-Y1
Over X2-X1 and then there is your slode
-10x+4.
5x-7x is -2.
-2x-8x is -10x.
you cannot simplify the 4
alternatively, you could write -10x+4 as
-2(5x-2)